Sandifer Syndrome: A continuing problem of misdiagnosis - Kabakus, Nimet; Kurt, Abdullah (Wiley, 2006)
Background: Sandifer Syndrome is an uncommon clinical entity characterized by gastroesophageal reflux, irritability and abnormal movements of the body and contortions of the neck. The majority of paroxysmal cases, in particular, tend to show an association with epilepsy. Methods: The clinical, laboratory and 6-month observation results of the four patients (two boys, two girls) have been presented. Results: The 6-month prospective observation/treatment of four patients aged between 2 and 14 months (mean age, 6.5 +/- 5.2 months) with a diagnosis of Sandifer Syndrome has been investigated. Due to paroxysmal extensor jerks, two of the patients were misdiagnosed with infantile spasm and they were treated accordingly. In the clinical observations of the patients, abnormal neurobehavioral attacks (irritability, crying, head/eye version, torticollis, extensor spasm and dystonic posture) 5-10 times daily were observed. In two of the patients, motor growth retardation was observed, in one patient, bronchospasm attacks were observed, and in all the patients iron deficiency anemia was observed. The electroencephalograms of the patients which were taken during the routine, sleepless and paroxysmal behaviors were normal; the gastroesophageal scintigraphies were positive in the manner of reflux. Management of the infant with gastroesophageal reflux disease, in addition to nonpharmacological interventions pharmacologic therapy, including metoclopramide HCl and Fe (6 mg/kg per day, oral) was useful for the patients, and their paroxysmal attacks decreased dramatically (0-2 attacks/day). Conclusions: These findings suggest that infants or children with these atypical movements should be evaluated for Sandifer Syndrome. Expensive and comprehensive neurologic examination may be unnecessary. Early diagnosis permits prompt treatment and relief of the problem. Medical management is usually successful.
Keywords: children; gastroesophageal reflux disease; Sandifer Syndrome; seizure